A correlational study of EFL learners’ language proficiency with their beliefs and language learning strategies / Xiang Yang - Xiang, Yang (2015)
The present study aims to identify learners’ beliefs and language learning strategies as well as their proficiency of English language, focusing on postgraduate students from China studying English in the Malaysian context. Both quantitative and qualitative methods were utilized. The questionnaire of BALLI (Beliefs About Language Learning Inventory) established by Horwitz (1988) and SILL (Strategy Inventory of Language Learning) by Oxford (1990) were delivered to 82 participants, among whom 10% were interviewed. Finding released the fact that participants have strongest beliefs of the nature of language learning and the lowest beliefs of the difficulty of language learning, and they used the compensatory strategies most and the affective strategies least. The insights and pedagogical implications of the study were put forward.